CIVILIAN POLITICIANS IN THE LAND OF GENERALS. THE COMPETITION FOR GOVERNMENT IN SONORA, 1929-1943 (Tzintzun, Revista de Estudios Históricos, 2023)
The objective of this article is to identify civil actors who began their politicalcareers between 1929 and 1943, to elucidate what made possible the transitionfrom governments presided over by veteran generals of the Revolution togovernments made up of civilian political professionals in tune with the nationalcontext, establishing a generational change whose members were defined ascivilians, who presented themselves as “technicians dedicated to nationalredemption through knowledge and loyalty to the president”.
Keywords: civil politicians; military politicians; Sonora; post-revolution